Five new species and one new subspecies of Micronoctuidae from China, with a checklist of Chinese species, including Taiwan (Lepidoptera: Noctuoidea, Micronoctuidae) - Fibiger, Michael; Han, Hui-Lin; Kononenko, Vladimir S. (Zootaxa, 2011)
Five new species and one subspecies of the family Micronoctuidae (Lepidoptera, Noctuoidea) (Bellulia bibella sp. n., Parachrostia pura sp. n., Tactusa virga sp. n., T. flexus sp. n., T. brevis sp. n., and T. discrepans yunnanensis ssp. n.) are described from South China (provinces Yunnan and Guizhou). Three species, Mimachrostia fasciata Sugi, 1982, T. discrepans Fibiger, 2010 and T. pars Fibiger, 2010 are reported from China for the first time. An updated checklist of the Micronoctuidae from China, including Taiwan is presented consisting of 28 species and 2 two subspecies.